Diabetic retinopathy: pathogenesis, pathophysiology, and treatment - Yudistira, Yudistira; Hendrawan, Kevin Anggakusuma; Andayani, Ari; Suryathi, Ni Made Ari (Faculty of Medicine, Universitas Trisakti, 2025)
Diabetic retinopathy (DR) is the most common microvascular complication of diabetes mellitus (DM) and one of the leading causes of vision impairment worldwide. Prolonged hyperglycemia initiates a cascade of molecular events including chronic inflammation, oxidative stress, advanced glycation end products, and the activation of plasma kallikrein and protein kinase C signaling pathways, which leads to endothelial damage and pericyte loss. The resulting endothelial barrier dysfunction promotes serum leakage and retinal edema, while advanced disease stages are characterized by ischemia-driven retinal neovascularization mediated by elevated intraocular vascular endothelial growth factor (VEGF) levels. Current therapeutic strategies for diabetic retinopathy include laser therapy, intravitreal administration of anti-VEGF agents or corticosteroids, and vitreoretinal surgery. Despite their efficacy, a number of patients experience suboptimal responses. Consequently, novel therapeutic approaches are under investigation, including alternative anti-angiogenic agents, gene therapies, and visual cycle modulators currently undergoing clinical trials. A comprehensive understanding of the pathogenesis and pathophysiology of diabetic retinopathy is essential to improve existing treatment modalities and address current limitations in patient outcomes. In this review, we systematically searched and analyzed articles published in English from 2014 to 2024 using PubMed, ScienceDirect, SpringerLink, and Google Scholar. Relevant search terms included “diabetic retinopathy,” “pathophysiology,” “pathogenesis,” “treatment,” and “diabetic macular edema.” This review presents recent insights into the pathogenesis of diabetic retinopathy, including oxidative stress, inflammation, and neurodegeneration, followed by an overview of its pathophysiology such as microvascular dysfunction and neovascularization. Finally, current and emerging treatment modalities, encompassing both pharmacological and surgical approaches, are discussed. This structured approach provides essential background to understand the complexity of diabetic retinopathy and recent advances in its management.